Inovasi Madrasah Melalui Penyelenggaraan Madrasah Riset - Hidayati, Umul (Badan Litbang dan Diklat Kementerian Agama RI, 2019)
AbstractThe research entitled Madrasah Innovation Through the Implementation of Madrasa Research (Case Study at MAN 1 Jembrana Bali) was motivated by the 2013 Ministry of Religion's Suryadarma Ali policy on the Research Madrasah Program. But apparently this policy is not accompanied by other policies that support it such as the preparation of implementation guidelines as a reference for the implementation, budgeting policies, provision/guidance of personnel, and the provision of adequate infrastructure. This then raises problems for madrasas that are starting to pilot research madrasas, so that the implementation cannot be carried out optimally. This study aims to see how the implementation of research madrassas in MAN 1 Jembrana is seen from several components such as infrastructure, staffing, financing, curriculum and madrasa head policies in administration. This study uses qualitative methods, with approaches phenomenological and socio historical. Data collection was carried out through in-depth interviews, participatory observation, and document study. The results showed that the pioneering research madrasas at MAN 1 Jembrana had been carried out seriously, but the research activities had not been running optimally because there were still several obstacles such as the lack of a special research budget available from DIPA, there was no special research space available, there was no available research supervisors, limited laboratory staff, and the absence of operational guidelines/technical guidelines as guidelines for implementation.Â AbstrakPenelitian berjudul Inovasi Madrasah Melalui Penyelenggaraan Madrasah Riset (Studi Kasus di MAN 1 Jembrana Bali) dilatarbelakangi oleh adanya kebijakan Kementerian Agama Suryadarma Ali tahun 2013 tentang Program Madrasah Riset. Namun ternyata kebijakan ini tidak dibarengi dengan kebijakan lain yang mendukungnya seperti penyusunan pedoman pelaksanaan sebagai acuan penyelenggaraan, kebijakan penganggaran, penyediaan/pembinaan ketenagaan, maupun penyediaan sarana prasarana yang memadai. Hal ini kemudian menimbulkan persoalan bagi madrasah-madrasah yang mulai melakukan rintisan penyelenggaraan madrasah riset, sehingga dalam penyelenggaraannya tidak dapat dilakukan secara maksimal. Penelitian ini bertujuan untuk melihat bagaimana penyelenggaraan madrasah riset di MAN 1 Jembrana dilihat dari beberapa komponen seperti sarana prasarana, ketenagaan, pembiayaan, kurikulum dan kebijakan kepala madrasah dalam penyelenggaraan. Penelitian ini menggunakan metode kualitatif, dengan pendekatan fenomenologis dan sosio historis. Pengumpulan data dilakukan melalui in-depth interview, participatory observation, dan document studies. Hasil penelitian menunjukkan bahwa rintisan penyelenggaraan madrasah riset di MAN 1 Jembrana sudah dilaksanakan dengan serius, namun kegiatan riset belum berjalan maksimal karena masih adanya beberapa kendala seperti belum tersedia anggaran khusus riset dari DIPA, belum tersedia ruang khusus riset, belum tersedia tenaga pembimbing riset, terbatasnya tenaga laboran, dan belum adanya juklak/juknis sebagai pedoman penyelenggaraan.